Klausula Baku dalam Kontrak Perdagangan yang dibuat Melalui Sistem Elektronik - Prakasya, Anas Rafi; Imron, Ali; Rahayu, Dewi Ayu; Sariwati, Retno; Anggriawan, Ferry (Bhirawa Law Journal, 2024)
The rapid development of technology has encouraged progress in the trade sector, necessitating the utilisation of electronic system technology to facilitate trade with all consumers from all over the globe. Consequently, business actors have employed electronic trade contracts in their efforts to reach all consumers from all over the world. In order to enhance efficiency, it is not uncommon for business actors to utilise a standard agreement containing standard clauses in conducting trade through electronic systems. The Standard Agreement is not prohibited by law; however, there is a clause that is prohibited by law, namely the Standard Agreement is prohibited from containing an exoneration clause. The purpose of this research is to identify the mechanism for creating electronic commerce contracts and the legal consequences resulting from exoneration clauses in the context of electronic commerce contracts. The research method employed is the Normative Law Research Method with a statute approach and a conceptual approach. The results of the research indicate that the mechanism for forming electronic trade contracts for goods or services, as regulated in PP No. 80 of 2019, begins with advertising, offering, acceptance, confirmation, followed by payment, delivery of goods or services, cancellation and dispute provisions. Furthermore, the legal consequences arising from the exoneration clause are null and void in accordance with what is regulated in Law No. 08 of 1999, namely in Article 18. PMSE Electronic Contract which results in losses to consumers, the standard contract maker can be retrieved to the Minister of Trade or BPSK